HARQ aware scheduling algorithm for the downlink LTE system - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan; Basukala, Riyaj; Afrin, Toyoba Sohana (IEEE, 2011)
To ensure an efficient and reliable data transmission over the error-prone downlink long term evolution (LTE) system, packet scheduling is tightly-coupled with adaptive modulation and coding (AMC)scheme and hybrid automatic repeat request (HARQ)process. Most of the packet scheduling algorithms proposed in the literature either fail to incorporate HARQ, or even if they do, these algorithms are not suited for delay sensitive guaranteed bit rate (GBR) services. A new packet scheduling algorithm that prioritizes HARQ users is proposed in this paper to support a delay sensitive GBR service. Simulation results show that this algorithm outperforms modified-largest weighted delay first (M-LWDF) algorithm by minimizing the number of lost packets, maintaining a low queuing delay and maximizing effective user throughput.